Integration Of Genetic And Nutritional Factors In The Production And Quality Of Dairy Goat Milk: A Review: Integrasi Faktor Genetik Dan Nutrisi Dalam Produksi Dan Kualitas Susu Kambing Perah : Review - Karni, Ine; Amalyadi, Rezki; Aminurrahman, Aminurrahman; Wandira, Ica Ayu; Gifari, Zaid Al; Septian, I Gede Nano; Anwar, Khairil (Buletin Peternakan Tropis, 2025)
The need for animal protein in Indonesia continues to increase, driving the popularity of goat milk as an alternative to cow's milk that is easier to digest and has health benefits. This study aims to review genetic and nutritional factors that affect the production and quality of dairy goat milk. The method used is a literature review of relevant scientific sources. Data analysis was carried out qualitatively. The results of the study indicate that genetic and nutritional factors play a major role in goat milk production. Imported goats such as Alpine (2,633 liters/lactation) and Saanen (2,621 liters/lactation) are more productive than local breeds such as Sapera (264.6 liters/lactation) and Peranakan Etawa (154.3 liters/lactation), supported by strict genetic selection and optimal maintenance management. Milk composition also varies, with Senduro goats having the highest total solids (14.30%), protein (3.74%), and fat (6.40%) compared to Alpine. Nutrition plays an important role in supporting milk production, with high protein sources such as lamtoro (32.0%) and turi (31.29%), as well as fat from turi (7.57%) and indigofera (6.15%) which increase milk fat content. Genetic and nutritional factors affect the production and quality of goat milk, with imported goats being more productive and Senduro goats being superior in milk composition. Proper feed and good management improve milk quality and livestock health. Understanding these genetic and nutritional factors is expected to be the basis for efforts to increase the productivity and quality of dairy goat milk in Indonesia